UJI ORGANOLEPTIK NUGGET DAGING DADA ITIK AFKIR DENGAN JENISDAN DOSIS TEPUNG YANG BERBEDA - Nurina Rahmawati; Agung Budiyanto (Jurnal Ilmiah Fillia Cendekia, 2017)
One of the resilience and diversification program of food were supplying and using local meat. Duck’s meat was soource of highly animal protein, but less of idea to process that meats. Nuggets was the produst processed meat that well liked many people. So expcted an be increase the economic of society. This research conducted at the campus of the Islamic University Kadiri on 29 april 2015 and was herped by 30 panelist. The purpose of this study to determine the species and levels or the different flour in nuggets ducks so that consumers prefer. The data obtained were analized using a completely randomized design analysis and if there is a noticeable difference then proceed to test LSD. The result showed that the species and levels or the different flour in nuggets ducks gave highly significant (P<0,01) for organoleptic tests include color, aroma, taste and texture. The conclusion of this research was the panelis liked the use of 20% level of flour in nuggets ducks